ANALISIS PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), NET PROFIT MARGIN (NPM), RETURN ON ASSET (ROA) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Pertambangan Periode 2012-2014) - Pamungkas, Yudha Aji; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2016)
The value of return on stock in mining companies keeps increasing annually during the research period of 2012 to 2014. The increase in return indicates that mining companies are able to either increase the profit or decrease the loss. Despite the increase in return, the Current Ratio, Debt to Equity Ratio, Net Profit Margin, Return on Assets, and Total Asset Turnover fluctuate annually during the research period. Â This study aims to determine the influence of Current Ratio (CR), Debt To Equity Ratio (DER), Net Profit Margin (NPM), Return on Assets (ROA) and Total Asset Turnover (TATO) to return stock in mining companies listed on the Stock Exchange at 2012-2014.The sample contains mining companies listed on the Indonesia Stock Exchange in the period 2012-2014 using purposive sampling. There are 30 companies that qualify as research samples. The analysis method used in this research is autocorrelation test, normality test, multiple regression analysis and analysis of kindness models.Based on the results of the study indicate that the Current Ratio (CR) has no effect on stock returns, Debt To Equity Ratio (DER) has no effect on stock return, Net Profit Margin (NPM) has positive effect on stock return but not significant, Return on Assets (ROA) does not effect on stock returns and Total Asset Turnover (TATO) does not effect on stock returns.